Sistem Pelaksanan Pelayanan Administrasi Terpadu Kecamatan (Paten) Tahun 2017 Di Kecamatan Payangan Kabupaten Gianyar - Pramana Putra, I Gst Ngurah Agung Dedy; Winaya, I Ketut; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2018)
ABSTARCT The Government has launched the Regulation of the Minister of Home Affairs No.4 of 2010 on the existence of PATEN guidance to improve a potential on service, especially to the service is administrative. Gianyar District Government together with District is very pro active in supporting the mandate of the Act by doing Technical, Substantive and Administrative preparation to prepare and support the implementation of District Integrated Administration Service (PATEN). Factors supporting success in the Implementation of District Integrated Administration Service (PATEN) in Payangan District Gianyar Regency that is due to government support, employee support and support from the community. Keywords: : Principles of Public Service, Quality of Service, PATEN Systems.